DINAMIKA SIKLON TROPIS DI ASIA TENGGARA MENGGUNAKAN DATA PENGINDERAAN JAUH - Haryani, Nanik Suryo; Zubaidah, Any (MAJALAH ILMIAH WIDYA, 2012)
Tropical cyclone is the form of extreme weather disturb. The growth of tropical cyclone is originated by tropical depressionor the center of an intensive low pressure above the ocean, triggering convection process and the intensive forming of cloud. Theaim of the research is to obtain the information of the extreme weather condition in the form of tropical depression and tropicalcyclones particularly the movement location of tropical cyclones and the influence coverage area in Indonesia. This method usedobservation and analyzing the impact of tropical cyclones in Indonesia area, and mapping its position based on latitude and longitudeof cyclone Centrum. The result of tropical cyclone monitoring in 2010 shows that tropical cyclone in Southern Indonesian area orIndian Ocean lasted in January, part of March and December 2010. Meanwhile, the tropical cyclone in Northern Indonesian areaon South China Sea and West Pacific was lasted in April , May, July, August, September, October, November and part of March 2010.Tropical cyclone on March 2010 did not show an orderly pattern. On May 2010, the tropical cyclones are simultaneously happen inthe northern and southern of Indonesia. In 2010 the concentration of tropical cyclone is heavily taken place in northern part ofIndonesia.